Pengaruh Perceived Ease of Use, Perceived of Usefulness dan Financial Risk Terhadap Intention to Use Pada Booking.com di Kabupaten Badung - Made Uttari Pitanatri; NMS Wijaya (JURNAL MASTER PARIWISATA, 2021)
Online reservation has been gives a easiest way for the tourist interm of booking an accomodation. Ease of use, and perceived of usefullness has been considered as a fundamental concern on decision making in using the online system. Booking.com is one of the online system that frequently used by the tourist. The study aimed to eximine the charasteristic of booking.com user, the effect of perceived ease of use, perceived of usefulness and financial risk om intention to use in Badung Regency. To investigate the hypotheses of the research, data was collected from booking.com user in Badung Regency. A survey was conducted with a sample size of 65 tourist and analized by multiple regresion analysis. The study revealed that perceived ease of use, perceived of usefulness and financial risk positively affect intention to use. Keywords: financial risk, intention to us, perceived ease of use and perceived of usefulness